2007
DOI: 10.1136/oem.2006.030130
|View full text |Cite
|
Sign up to set email alerts
|

Mortality study update of acrylamide workers

Abstract: Objective: The authors examined the long-term health effects of occupational exposure to acrylamide among production and polymerisation workers. Methods: An earlier study of 371 acrylamide workers was expanded to include employees hired since 1979. In this updated study, 696 acrylamide workers were followed from 1955 through 2001 to ascertain vital status and cause of death. Exposure to acrylamide was retrospectively assessed based on personal samples from the 1970s onwards and area samples over the whole stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…Although the route of exposure differs, these results are in line with studies on occupational acrylamide exposure, which did not show excess brain cancer incidence in association with acrylamide exposure (11,12). The number of cases in the analyses was modest, especially in the subgroups based on histology.…”
Section: Discussionsupporting
confidence: 77%
“…Although the route of exposure differs, these results are in line with studies on occupational acrylamide exposure, which did not show excess brain cancer incidence in association with acrylamide exposure (11,12). The number of cases in the analyses was modest, especially in the subgroups based on histology.…”
Section: Discussionsupporting
confidence: 77%
“…Based on the IARC classification of AA and the available evidence the authors concluded that the strength of evidence for AA and pancreatic cancer was suggestive. The CONTAM Panel noted, however, that the authors were not able to include the evidence of the extended follow-up of the two cohorts that were published in 2007 (Marsh et al, 2007;Swaen et al, 2007).…”
Section: Occupational Studies and Cancermentioning
confidence: 99%
“…As compared to dietary studies, occupational studies are likely to measure AA exposure more accurately. Moreover, workers have been exposed to higher doses of AA (particularly in the past, Swaen et al, 2007), although individual occupational exposure may be variable and limited in time. Accordingly, various studies which have measured AA-and GA-Hb adducts in different populations (as biomarkers for AA exposure) showed that occupational exposures to AA have been considerably higher than in the general population, either in non-smoking or smoking groups.…”
Section: Considerations On the Interpretation Of The Epidemiological mentioning
confidence: 99%
“…Animal studies have shown positive dose-response relationships between acrylamide given in drinking water and cancer in multiple organs in both mice and rats (9)(10)(11)(12), among which were several hormone-sensitive organs, such as the mammary glands and the uterus. However, studies on humans with occupational acrylamide exposure have been negative thus far, apart from an increased risk of pancreatic cancer, but this was based on a small number of cases (13)(14)(15)(16)(17)(18). Dietary acrylamide intake and its relation with various types of cancer have been studied in a few case-control studies (19)(20)(21) and only two prospective cohort studies on breast and colorectal cancer (22,23).…”
Section: Introductionmentioning
confidence: 99%